The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1104/pp.105.072983
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Deficiency Disrupts Metabolism of Ureides, Amino Acids, and Organic Acids of Young Pecan Foliage

Abstract: The existence of nickel (Ni) deficiency is becoming increasingly apparent in crops, especially for ureide-transporting woody perennials, but its physiological role is poorly understood. We evaluated the concentrations of ureides, amino acids, and organic acids in photosynthetic foliar tissue from Ni-sufficient (Ni-S) versus Ni-deficient (Ni-D) pecan (Carya illinoinensis [Wangenh.] K. Koch). Foliage of Ni-D pecan seedlings exhibited metabolic disruption of nitrogen metabolism via ureide catabolism, amino acid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
1
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(110 citation statements)
references
References 38 publications
3
96
1
6
Order By: Relevance
“…The down-regulated citric acid is likely evidence that nCu influences the availability of acetylCoA. 63 Interestingly, most of the metabolites related to carbohydrate metabolism are reported to be a response to iron deficiency in the leaves and xylem sap of several plant species, including peach, tomato, and sugar beet. 64 It has been demonstrated that the response of leaves to iron deficiency is up-regulation of carbohydrates and TCA cycle metabolites and N-related metabolites.…”
Section: Biological Pathways Impacted By Ncumentioning
confidence: 99%
“…The down-regulated citric acid is likely evidence that nCu influences the availability of acetylCoA. 63 Interestingly, most of the metabolites related to carbohydrate metabolism are reported to be a response to iron deficiency in the leaves and xylem sap of several plant species, including peach, tomato, and sugar beet. 64 It has been demonstrated that the response of leaves to iron deficiency is up-regulation of carbohydrates and TCA cycle metabolites and N-related metabolites.…”
Section: Biological Pathways Impacted By Ncumentioning
confidence: 99%
“…However, the systemic, nonpoint source effects observed in plants upon application of micronutrients suggest that, in addition to pathogen toxicity, they might also directly be involved in physiological processes that confer plant resistance to diseases. Such processes include stimulating the production of antioxidants and other pathogen inhibitory compounds, influencing lignin and suberin biosynthesis to toughen cell walls and reduce pathogen infiltration, and modulating N metabolism in the plant (Huber and Wilhelm 1988;Römheld and Marschner 1991;Boyd et al 1994;Bai et al 2006;Evans et al 2007;Stangoulis and Graham 2007;Taran et al 2014;Servin et al 2015a). Notably, B's involvement in cell wall regulation is related to the modulation of Ca balance in the cell wall, helping in the formation of calcium pectate that confer rigidity to the plant (Stangoulis and Graham 2007), which otherwise would be more easily weakened by disease or drought stress.…”
Section: Physiological Roles and Roles In Abiotic And Biotic Stress Mmentioning
confidence: 99%
“…No doubt, the occurrence of HMs can be both beneficial and harmful for plants (Meuwly & Rauser 1992;Rauser & Meuwly 1995;Schützendübel & Polle 2002;Seregin & Kozhevnikova 2006). Unlike Ni, that is a component of urease and at low concentrations stimulates growth of some plants (Bai et al 2006), Cd is not involved in any known physiological function within a plant body and has been reported to cause deleterious effects on plants (Tran & Popova 2013).…”
Section: Introductionmentioning
confidence: 99%